Analisa Aktivitas Antioksidan Ekstrak Biji Nangka (Artocarpus heterophyllus Lam) dengan Metode Frap (Ferric Reducing Antioxidant Power) - Maulana K, Andi; Naid, Tadjuddin; Dharmawat, Dewi Tri; Pratama, Mamat (bionature, 2019)
Abstract. Our daily life is very often in contact with free radicals which is one of the causes of disease. To neutralize the work of free radicals Antioxidants are needed. Antioxidants are compounds that donate one or more electrons to oxidant compounds. Jackfruit seeds often become waste that is not used by the community. Jackfruit seeds contain chemicals such as flavonoids, saponins and steroids. This study aims to study and determine the antioxidant activity of jackfruit seed extract (Artocarpus heterophyllus Lam.) By the FRAP method (Ferric Reducing Antioxidant Power). The sample was extracted using the maceration method and the extract obtained was analyzed using a UV-Vis spectrophotometer at a wavelength of 716.20 nm using quercetin as a comparison. Based on data analysis, the average value of antioxidant activity of jackfruit seed extract (Artocarpus heterophyllus Lam.) Amounts to 4.8819 mgQE / g extract, meaning that each gram of extract contains 4.8819 mgQE which is in accordance with quercetin standards. This shows that jackfruit seed extract has antioxidant activity which is equivalent to quercetin.Keywords: Antioxidants, Jackfruit Seeds (Artocarpus heterophyllus Lam.), FRAP, UV-Vis Spectrophotometer